Territorios de diferencia : lugar, movimientos, vida, redes - Escobar, Arturo, 1951- (Editorial Univesidad del Cauca, 2018)
In this book, the author analyzes the politics of difference enacted by specific place-based ethnic and environmental movements in the context of neoliberal globalization. His analysis is based on his many years of engagement with a group of Afro-Colombian activists of Colombia's Pacific rainforest region, the Proceso de Comunidades Negras (PCN). Escobar offers a detailed ethnographic account of PCN's visions, strategies, and practices, and he chronicles and analyzes the movement's struggles for autonomy, territory, justice, and cultural recognition. Yet he also does much more. Consistently emphasizing the value of local activist knowledge for both understanding and social action and drawing on multiple strands of critical scholarship, Escobar proposes new ways for scholars and activists to examine and apprehend the momentous, complex processes engulfing regions such as the Colombian Pacific today.